Rancang Bangun Aplikasi Pendeteksi Tipe Dan Nilai Resistor Berbasis Android - Pratama Andika, I Putu; Agung Bayupati, I Putu; Ayu Wirdiani, Ni Kadek (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2015)
Android can be identified as the phone with the ability a high degree resembling computer, by making use of technological progress, an error in the determination of type and value of obstruction from resistors led a series of electronics result of the damage can be avoided, this is because of a resistor having the function of as parapet an electric current or as voltage divider of the series, detection so that the application of type and value of resistor able to contribute to the introduction of a resistor, by using processing tecnology digital image that is a method of hsv ( hue saturation value ). Hsv useful as a limit of a color become a reference of the rings of color resistor, by applying this method application can do the introduction of against resistors diinputkan, to then give them the information relating to a type and value of a resistor. It has the percentage research success in the introduction of the value and type resistor by 57 %, to misidentified 30 % and not being recognized of 13 % .
Keywords: Resistor; HSV; Android